UJI EFEKTIVITAS EKSTRAK BAWANG MERAH (Allium cepa ), BAWANG PUTIH (Allium sativum ), DAN BAWANG BOMBAY (Allium cepa ) TERHADAP LINTAH LAUT HIRUDINEA (Zeylanicobdella arugamensis) SECARA IN VITRO - Zafran; Ketut Mahardika; Indah Mastuti; Nadyasari, Kadek Ratih (Universitas Hang Tuah, 2021)
Grouper is an important fish species of mariculture in Indonesia. One of production constraint in grouper culture is mortality due to marine leech (Zeylanicobdella arugamensis) infection. The objective of this study was to determine the effectiveness of three different onions (shallot, garlic, and leek) extract with different concentrations and immersion time against marine leech under laboratory condition. The concentration of onion extract tested were 100%, 50%, 25%, 12.5%, 6.25%, 3.12%, and 1.6%, respectively. Sterile sea water without onion extract was used as control. The mortality of leech in each concentration was observed every 30 minutes for 2 hours by transfer them into petri dish filled with 50 ml of sterile sea water. Result showed that garlic extract more effective than shallot and leek against marine leech. Garlic extract at concentration of 3.12% killed 100% of marine leech after 60 minutes immersion, whereas leek extract effective killed 100% of marine leech at concentration of 12.5% after 60 minutes and shallot at concentration of 25%, respectively. Garlic extract showed good potency to be used as a herb to control marine leech infection in grouper culture.